Partisipasi Perempuan dalam Proses Pengambilan Keputusan di Desa Pledo - Gladies Damainantha Nalle; Stephanie Perdana Ayu Lawalu; Yasinta Yunrianto Palan Peten (Universitas Kristen Indonesia Toraja, 2024)
Increasing women's participation in decision-making processes at the village level is a challenge that requires cooperation and perseverance between the government and women. The case study in Pledo Village shows that women's participation is quite good with their active involvement in village forums and meetings held by village officials. Women's voices have been heard and some of them have been accepted according to the needs of the village. The socialization activity in Pledo Village on May 6 2024 aims to increase women's awareness of the importance of participation in village activities. This activity was attended by women's representatives from two nearby hamlets. The discussions that took place revealed several obstacles to women's participation, such as feelings of inferiority caused by low levels of education, feelings of laziness, and status as newcomers. The proposed solution is to increase involvement in PKK activities so that they are more involved in activities and meetings in the Village and more active in activities and forums carried out to make decisions for the sake of the Village. Increase familiarity and knowledge of things that women need to do in participation in order to eliminate feelings of inferiority regarding the level of individual education in the Village development process. Reactivating existing weaving groups is a solution so that women who are immigrants can join and become more familiar because joining these groups is a process of getting to know local residents. This socialization received support from the village government as an effort to make women aware of the importance of their role in the decision-making process.